ok sooo bascally first you need to decide what way you are using. Since you cant factor it, you can either use quadratic formula or completing the square. I will be completing the square.

First subtract 25 on both sides. this gives you x^2 + 12x = -10.

Then we need to divide 12 by 2 to fill this first gap ---> (x+_)^2 = -10 + _. 12/2 is 6 so it becomes (x+6)^2 = -10 + _

The next gap will be the 6 squared. 6 squared is 36, so it will become (x+6)^2 = -10+36 which is (x+6)^2 = 26

Then we need to take the square root of each side. This results in x+6 = + or - \(\sqrt{26}\)

After that we subtract by 6 on both sides, so we get x= -6 + or - \(\sqrt{26}\), which is our final answers. Another way to write it is {-6 - \(\sqrt{26}\), -6 +\(\sqrt{26}\)}

Hope this was helpful!